Determination of the operational parameters values for Airbus A300-600ST Beluga aircraft on the basis of CFD tests - Nowacki Marcin; Olejniczak Damian (MATEC Web of Conferences, 2022)
The article presents a method for estimating the values of basic operational and aerodynamic parameters of an aircraft. It contains a multistage analysis of CFD test results for the Beluga Airbus A300-600ST model. The first step of the method is to determine the values of aerodynamic parameters such as lift coefficient, drag coefficient, lift force and drag force in specific flight conditions. A comparative analysis of the coefficients of lift and drag force depending on the angle of attack of the aircraft allowed the estimation of the optimal angle of attack of the Airbus A300-600ST Beluga. In the next step, the operational values and the maximum flight ceiling of the aircraft were determined. For this purpose, the results of CFD simulation tests for the optimal angle of attack of the aircraft were used. This article allowed determining the characteristics of the components of aerodynamic force of an airplane depending on the angle of attack, flight altitude and flight speed, determining the optimal angle of attack of the aircraft and calculation of the optimal and maximum flight ceiling values of the Airbus A300-600ST Beluga.